Environmental and animal characteristics as factors associated with American cutaneous leishmaniasis in rural locations with presence of dogs, Brazil. - Norberto Assis Membrive; Gesse Rodrigues; Kezia Peres Gualda; Marcos Vinícius Zandonadi Bernal; Diego Molina Oliveira; Maria Valdrinez Campana Lonardoni; Ueslei Teodoro; Jorge Juarez Vieira Teixeira; Thaís Gomes Verzignassi Silveira (PLoS ONE, 2012)
The aim of the study was to investigate the importance of dogs, other domesticated animals and environmental characteristics as risk factors in the epidemiology of American cutaneous leishmaniasis (ACL). A retrospective survey of cases of human ACL in the last ten years and visits to homes in rural locations were carried out in the municipality of Arapongas (southern Brazil) from 2008 to 2010. ACL in humans was significantly associated with a distance of up to 25 meters from the residence to a forest area (OR 5.08; 95% CI: 1.35-21.04), undergrowth area (OR 6.80; 95% CI: 1.69-45.33) and stream (OR 5.87; 95% CI: 1.15-24.59); banana plants near the residence (OR 5.98; 95% CI: 1.49-39.84), absence of ceiling below the roof in the residence (OR 7.30; 95% CI: 1.26-158.1), the dumping of trash in the forest area (OR 26.33; 95% CI: 7.32-93.46) and presence of ACL in dogs in the surrounding area (OR 4.39; 95% CI: 1.37-13.45). In dogs, ACL was associated with a distance of 25 to 50 meters and 51 to 100 meters, respectively, from the residence to a forest area (OR 2.59; 95% CI: 1.08-5.98; OR 3.29; 95% CI: 1.64-6.62), the presence of a stream up to 25 m from the residence (OR 6.23; 95% CI: 2.34-16.54) and banana plants near the residence (OR 0.45; 95% CI: 0.25-0.80). In the locations studied in the municipality of Arapongas (Brazil), the results reveal that canine infection increases the risk of human infection by ACL and the characteristics surrounding the residence increase the risk of infection in both humans and dogs. Thus, integrated environmental management could be a useful measure to avoid contact between humans and phlebotomines.